(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mir Qamruddin Khan Nizam-ul-Mulk Asaf Jah-I established a new dynasty is called Saltanath-E-Asafia in 1724 AD. The first capital was Aurangabad. After shifted to Hyderabad in the period of Nizam Ali Khan-II. The early period of Mir Qamruddin Khan was spent in battles. Therefore, not many madrasas are mentioned during his period. "Paigah" was established during the reign of Nizam Ali Khan-II